Exome Sequencing Reveals Primary Immunodeficiencies in Children with Community-Acquired Pseudomonas aeruginosa Sepsis - Asgari, Samira; McLaren, Paul J.; Peake, Jane; Wong, Melanie; Wong, Richard; Bartha, Istvan; Francis, Joshua R.; Abarca, Katia; Gelderman, Kyra A.; Agyeman, Philipp; Aebi, Christoph; Berger, Christoph; et al. (Frontiers in Immunology, 2016)
One out of three pediatric sepsis deaths in high income countries occur in previously healthy children. Primary immunodeficiencies have been postulated to underlie fulminant sepsis, but this concept remains to be confirmed in clinical practice. Pseudomonas aeruginosa (P. aeruginosa) is a common bacterium mostly associated with healthcare-related infections in immunocompromised individuals. However, in rare cases, it can cause sepsis in previously healthy children. We used exome sequencing and bioinformatic analysis to systematically search for genetic factors underpinning severe P. aeruginosa infection in the pediatric population. We collected blood samples from 11 previously healthy children, with no family history of immunodeficiency, who presented with severe sepsis due to community-acquired P. aeruginosa bacteremia. Genomic DNA was extracted from blood or tissue samples obtained intravitam or postmortem. We obtained high-coverage exome sequencing data and searched for rare loss-of-function variants. After rigorous filtrations, 12 potentially causal variants were identified. 2 out of 8 (25%) fatal cases were found to carry novel pathogenic variants in primary immunodeficiency genes, including BTK and DNMT3B. This study demonstrates that exome sequencing allows to identify rare, deleterious human genetic variants responsible for fulminant sepsis in apparently healthy children. Diagnosing primary immunodeficiencies in such patients is of high relevance to survivors and affected families. We propose that unusually severe and fatal sepsis cases in previously healthy children should be considered for exome/genome sequencing to search for underlying primary immunodeficiencies.